2020
DOI: 10.31557/apjcp.2020.21.9.2697
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Industry Cancer Risk in Japan: A Multicenter Hospital-Based Case Control Study

Abstract: organic solvents (e.g., benzene, chloroform, and phenol), and asbestos(IARC, 1987). The risk may be linked with a combination of other exposures such as smoking or secondhand smoke (Alberg et al., 2013). It is important to account for the characteristics of carcinogen exposure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Utilizing ICOD-R occupational classification major groups, a relationship between occupations that harbor high physical activity and the reduction of cancer risk was demonstrated [12]. By comparing the categories included in the manufacturing industry division of ICOD-R, it was shown that ureter cancer incidence in workers engaged in electronics is higher than that in workers in food manufacturing [22]. Therefore, it is justified to add the industrial/occupational classification to the confounding factors of GWAS for the examination of the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing ICOD-R occupational classification major groups, a relationship between occupations that harbor high physical activity and the reduction of cancer risk was demonstrated [12]. By comparing the categories included in the manufacturing industry division of ICOD-R, it was shown that ureter cancer incidence in workers engaged in electronics is higher than that in workers in food manufacturing [22]. Therefore, it is justified to add the industrial/occupational classification to the confounding factors of GWAS for the examination of the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Kaneko et al used ICOD-R occupational classification major groups to demonstrate that occupations with high physical activity reduced the risk of cancer [ 27 ]. They also compared the categories included in the manufacturing industry division (Division E) of ICOD-R and noted that the incidence of ureter cancer in the electronics category is higher than that in the food manufacturing category [ 43 ]. Therefore, adding the industrial/occupational classification to the adjusting factors of GWAS, even if it is relatively rough, is considered to be meaningful in examining the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Oddone et al (2013) reported a case–control study in Italy that found that breast cancer incidence was associated with employment in textile, rubber, paper, and electrical manufacturing industries [ 18 ]. Kaneko et al (2020) conducted a case–control study investigating cancer risk among different manufacturing industries and found higher breast cancer risk among industries including clothing, chemicals, non-ferrous metals and products, and communication electronics, compared with a food manufacturing group [ 19 ]. Another study conducted in Canada found elevated breast cancer risk among female workers in plastics and rubber product fabricating industries [ 20 ].…”
Section: Discussionmentioning
confidence: 99%